Cardiac biomarkers following marathon running: is running time a factor for biomarker change? - Traiperm, N.; Chaunchaiyakul, R.; Burtscher, M.; Gatterer, H. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) and cardiac troponin T levels show a transient increase after marathon running. The aim of this study was to investigate whether running duration influences the patterns of changes in cardiac biomarkers.